Odpowiedzi

2009-12-10T19:14:01+01:00
A) 5(x⁴-4) = 5(x²-2)(x²+2)=5(x-pierwiastek z 2) (x+ pierwiastek z 2)

b)2x²(-2x²+13x-6)

c)2x³+6x+5x²+15
2x(x²+3)+5(x²+3)
(2x+5) ( x²+3)
(2x+5) (x-pierwiastek z 3) (x+ pierwiastek z 3)
Najlepsza Odpowiedź!
2009-12-10T19:15:23+01:00
A)5x⁴-20
5(x^4-4)
5(x^2-2)(x^2+2)
5(x-√2)(x+√2)(x^2+2)

b) -4x⁴+26x³-12x²
-x^2 (4x^2-26x+12)
∆=26^2-4*4*12=676-192=484
√∆=22
x_1=(26+22)/8=6
x_2=(26-22)/8=4/8=0,5
-x^2 (x-6)(x-0,5)

c)2x³+5x²+6x+15
2x(x^2+3)+5(x^2+3)
(2x+5)(x^2+3)
(x+2,5)(x^2+3)